Lintang and the brightest star - Moss, Tamara (North Sydney, NSW : Random House Australia, 2018)
As the conquering hold of the United Regions continues to spread, time is running out for Lintang, Captain Shafira and the crew of the Winda to find allies in their quest for peace. But when they arrive in war-torn Kaneko Brown, the local rebels are too scared to help. The Vierzans have summoned a category ten mythie that devours the star of anyone who dares stand against them. Worse, the mythie has been prophesied to mean the end of Captain Shafira. Lintang must find a way to stop the most dangerous mythie in the guidebook . . . or she'll lose her beloved captain forever.
Imprint: Random House Australia.
For primary school age.
Also available in hardcopy.
Keywords: Adventure stories; Children's stories; Pirates -- Juvenile fiction; Sea stories -- Juvenile fiction; Adventure stories; Children's stories; Fantasy & magical realism (Children's / Teenage); Juvenile Fiction - Science Fiction, Fantasy, Magic; Pirates; Sea stories; Australian; Electronic books; Fiction